Online survey among maritime pilots: job-related stress and strain and the effects on their work ability - Marcus Oldenburg; Jan Herzog; Filip Barbarewicz; Volker Harth; Hans-Joachim Jensen (Journal of Occupational Medicine and Toxicology, 2021)
Abstract Background Maritime pilots often navigate ships through challenging waterways. The required 24 h standby rotation system (ROS) poses a stressful working situation. This study aims to describe the current job-related stress and strain among maritime pilots and the effects on their work ability, taking into account the different rotation systems. Methods Within a cross-sectional survey, pilots of all German pilots’ associations were asked to complete an online questionnaire. The 1-week ROS (port pilots) was compared with the 4-month ROS (sea and canal pilots). The pilots’ subjective perception of stress and strain was assessed using an established ship-specific questionnaire. Daily sleepiness and work ability were examined respectively using the Epworth Sleepiness Scale (ESS) and the Work Ability Index (WAI). Results The study group consisted of 401 male German pilots with an average age of 48.5 years (participation rate 46.9%). More than 50% of the pilots evaluated irregular working hours as the main stressor in their job. 79.8% of the pilots (especially 4-month ROS) experienced high psychological demands in their workplace. 83.3% stated having regularly neglected their private obligations due to job assignments. Pilots from the 4-month ROS experienced insufficiently predictable free time and long operation times at a stretch as stressors (p < 0.001 and p = 0.037). Elevated daily sleepiness was found in 41.9% of the pilots. The overall evaluation of the WAI questionnaire showed good to very good work ability at 77.3%. Additionally, no significant differences in the daily sleepiness or the work ability were observed between the pilots of the different two ROS. Conclusions Due to their subjectively higher job-related mental demands, their disturbed work-life balance, and their long operation times at a stretch, it is likely that pilots from the 4-month ROS have significantly higher job stress compared to those in the 1-week ROS. However, this does not lead to more sleepiness or reduced work ability, which suggests that the pilots of this ROS are highly adapted to their working situation. Nevertheless, intervention measures with shortened ROS amongst sea and canal pilots’ associations should be tested in respect of benefit, practicability and acceptance by the pilots.